The Influence of Virtual Reality Technology on Purchase Intention through User Experience as an Intervening Variable in the Marketing Strategy of Samsung Products in the Virtual World: a Conceptual Paper - Afwa, Intan Lailya; Rubiyanti, Nurafni; Widodo, Arry; Silvianita, Anita (East Asian Journal of Multidisciplinary Research, 2024)
Virtual reality has come a long way in recent years, and its potential to revolutionize the world of marketing is becoming increasingly apparent. It offers an immersive and engaging new way to reach consumers. Samsung utilizes this technology to gain a significant advantage in competition. This study aims to determine the effect of virtual reality technology on purchase intention through user experience as an intervening variable in the marketing strategy of Samsung products in the virtual world. This type of research is quantitative research using the Structural equation modeling (SEM) method with the Partial Least Square (PLS) approach using SmartPLS software. With this research, it is hoped that it can contribute to improving marketing strategies for Samsung products through virtual reality technology.